Intestinal ultrasound in inflammatory bowel disease: When and how use it efficiently? - Parra Izquierdo, Viviana (2025)
In Latin America, the prevalence of Inflammatory Bowel Disease (IBD) has increased in recent years, creating a growing need for diagnostic tools both for its detection and for ongoing monitoring. Intestinal ultrasound (IUS) has become a well-established, non-invasive, accurate, and well-tolerated tool to evaluate IBD activity in real time—even during the same medical consultation. Available evidence supports its usefulness in accurately determining inflammatory activity and identifying associated complications. At the time of diagnosis and initiation of treatment, IUS has proven to be the ideal non-invasive study for close monitoring, assessing therapeutic response, and making early treatment adjustments. Multiple systematic reviews and meta-analyses have shown that its diagnostic accuracy is comparable to that of colonoscopy or magnetic resonance imaging. Additionally, IUS allows for therapeutic monitoring and prognosis assessment in a more accessible, non-invasive way, with greater patient adherence compared to other diagnostic modalities. This review article aims to analyze the optimal use of IUS and its current role in the management of patients with IBD.